2019
DOI: 10.1002/elps.201800508
|View full text |Cite
|
Sign up to set email alerts
|

Enantioseparation of tryptophan and its unnatural derivatives by nano‐LC on CSP‐teicoplanin silica based

Abstract: This work deals with the potentiality of nano liquid chromatography (Nano‐LC) for the chiral separation of racemic mixture of tryptophan and some selected derivatives by using 100 µm i.d. fused silica capillary packed with teicoplanin bonded to 5 µm diol silica stationary phase. The experiments were carried out by using a cheap and laboratory‐assembled nano‐LC–UV system. Elution was done in an isocratic mode using a polar organic mobile phase. In order to find the optimum chiral separation of the studied enant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…An essential aspect of the mobile phase composition study is the change of the organic, water, and additive content to enhance specific CSP‐analyte interactions, especially enantioselective ones. In our previous chiral studies, it has been reported that changing the composition of binary mobile ACN/water, MeOH/water [22], and MeOH/ACN [18] had a significant effect on the analytes’ k′ 1 and Rs .…”
Section: Resultsmentioning
confidence: 99%
“…An essential aspect of the mobile phase composition study is the change of the organic, water, and additive content to enhance specific CSP‐analyte interactions, especially enantioselective ones. In our previous chiral studies, it has been reported that changing the composition of binary mobile ACN/water, MeOH/water [22], and MeOH/ACN [18] had a significant effect on the analytes’ k′ 1 and Rs .…”
Section: Resultsmentioning
confidence: 99%
“…In less than 8 min, the MP containing 40 mM ammonium formate at pH 2.5 in ACN/water/acetone (60:30:10, v/v/v) at 520 nl/min attained baseline enantioresolution and excellent peak shape [70].…”
Section: Nano‐lcmentioning
confidence: 99%
“…Glycopeptide antibiotics, like vancomycin or teicoplanin, are used as CS (Table S3) [70][71][72][73][74][75][76]. Because of the synergism between specific interactions (e.g., hydrogen bonding, ionic, dipole-dipole, π-π, and so on) and the inclusion-complexation mechanism, these molecules with several asymmetric centers, charged groups, aromatic rings, phenolic, amide, and sugar substituents have a high capability to recognize different types of enantiomers.…”
Section: Cs Based On Macrocyclic Antibiotics Employing Nano-lcmentioning
confidence: 99%
“…A variety of chiral sensing approaches, including chromatography, capillary electrophoresis, and electrochemical and optical methods, have been developed for chiral discrimination of Trp enantiomers. Despite their efficacy, these methods usually rely on laborious pretreatments, expensive chiral columns, and lengthy procedures for preparing chiral probes.…”
Section: Introductionmentioning
confidence: 99%